OPTIMALISASI PERAN MAHKAMAH KONSTITUSI DALAM UPAYA MENERAPKAN CONSTITUTIONAL QUESTION DI INDONESIA GUNA MEMENUHI HAK ASASI BAGI WARGA NEGARA - Caroline Tresnoputri; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2021)
Every Indonesian citizen has the right to protection and legal certainty. One way that can be used is by submitting a constitutional question that can be done by a judge when examining a statutory regulation that is felt and believed to be inadequate and contrary to the Constitution of the Republic of Indonesia. In practice, the state has given and carried out constitutional questions, but legally, these rights do not accommodate them. In fact, one way that can be used to fulfill the constitutional rights of its citizens can be done with an institutional question. Therefore, this study will discuss the urgency of implementing constitutional questions in government. This research uses a normative juridical research method with a statutory approach. That the results of the research are that the constitutional rights of citizens are indispensable in order to provide and fulfill the rights of citizens in the judicial process. Thus, in this case, the Government is obliged to fulfill these rights by including constitutional questions in the laws and regulations.